A radio-emitting outflow produced by the tidal disruption event AT2020vwl - Goodwin, Adelle; Alexander, K.D.; Miller-Jones, James; Bietenholz, M.F.; van Velzen, S.; Anderson, Gemma; Berger, E.; Cendes, Y.; Chornock, R.; Coppejans, D.L.; Eftekhari, T.; Gezari, S.; et al. (2023)
A tidal disruption event (TDE) occurs when a star is destroyed by a supermassive black hole. Broad-band radio spectral observations of TDEs trace the emission from any outflows or jets that are ejected from the vicinity of the supermassive black hole. However, radio detections of TDEs are rare, with <20 published to date, and only 11 with multi-epoch broad-band coverage. Here we present the radio detection of the TDE AT2020vwl and our subsequent radio monitoring campaign of the outflow that was produced, spanning 1.5 yr post-optical flare. We tracked the outflow evolution as it expanded between 1016 and 1017 cm from the supermassive black hole, deducing it was non-relativistic and launched quasi-simultaneously with the initial optical detection through modelling the evolving synchrotron spectra of the event. We deduce that the outflow is likely to have been launched by material ejected from stream-stream collisions (more likely), the unbound debris stream, or an accretion-induced wind or jet from the supermassive black hole (less likely). AT2020vwl joins a growing number of TDEs with well-characterized prompt radio emission, with future timely radio observations of TDEs required to fully understand the mechanism that produces this type of radio emission in TDEs.